2016
DOI: 10.1038/srep27394
|View full text |Cite
|
Sign up to set email alerts
|

Design of an α-helical antimicrobial peptide with improved cell-selective and potent anti-biofilm activity

Abstract: AR-23 is a melittin-related peptide with 23 residues. Like melittin, its high α-helical amphipathic structure results in strong bactericidal activity and cytotoxicity. In this study, a series of AR-23 analogues with low amphipathicity were designed by substitution of Ala1, Ala8 and Ile17 with positively charged residues (Arg or Lys) to study the effect of positively charged residue distribution on the biological viability of the antimicrobial peptide. Substitution of Ile17 on the nonpolar face with positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 57 publications
4
114
0
Order By: Relevance
“…Compared with the parent peptide chensinin-1, the mutated peptides MC1-1, MC1-2, and MC1-3 demonstrated potent antimicrobial activities against all tested Gram-positive bacteria, with different activities against specific Gram-negative bacteria. To evaluate the overall antimicrobial activity, the geometric mean of the MIC values was calculated28. MC1-2 displayed much higher antimicrobial activity against the selected bacteria than MC1-1 and MC1-3.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the parent peptide chensinin-1, the mutated peptides MC1-1, MC1-2, and MC1-3 demonstrated potent antimicrobial activities against all tested Gram-positive bacteria, with different activities against specific Gram-negative bacteria. To evaluate the overall antimicrobial activity, the geometric mean of the MIC values was calculated28. MC1-2 displayed much higher antimicrobial activity against the selected bacteria than MC1-1 and MC1-3.…”
Section: Resultsmentioning
confidence: 99%
“…Mel possesses notoriously high lytic activity at both pH 7.4 and 5.0, whereas RV exhibits lower cytotoxic activity at pH 7.4 than Mel . The impact of Glu replacement on the ability of Mel and RV to disrupt the cell membrane was investigated by hemolytic assays.…”
Section: Resultsmentioning
confidence: 99%
“…Mel is an AMP with high lytic activity at neutral pH . The hemolysis assay demonstrated that 1.25 μM Mel induced 73% hRBC lysis at pH 7.4; however, 10 μM Mel induced lysis of only 50% hRBCs at pH 5.0.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations